Slashed: Insect Gazes, Point-of-View Perspectives, and the Rise of a Post/Human Vision in the Italian giallo - Jacob, Émilie (Quaderni d'Italianistica)

(untitled) (Iter Press, 2025)
Establishing an ecology of Italian horror by looking at Mario Bava’s A Bay of Blood (1971) and Dario Argento’s Phenomena (1985)—both of which feature insects’ first-“person” perspective shots, this paper traces the formation and subsequent development of a gaze in these films, one that disrupts the understanding of this gaze as human. From thematic concerns like ecology, entomology, and an emphasis on an anti-anthropomorphic gaze, we can begin to trace a resonance between the two films and their desire to expand vision. Examining early articulations of a posthumanist sensibility and vision in these films, this paper surveys the complex entanglements between Italian formulations of horror and violence, proposing the concept of an ‘insect gaze’ as a mediated gaze before exploring the terror, and possibilities, it engenders. Separated by more than a decade, the films present non-human gazes that trigger deep-seated anxieties specific to their historical context.